Extramedullary Plasmacytoma of the Tonsil - Huoh, Kevin C.; Van Zante, Annemieke; Eisele, David W. (Case Reports in Otolaryngology, 2011)
Plasma cell tumors are a diverse group of neoplasms characterized by monoclonal proliferation of plasma cells. Extramedullary plasmacytoma (EMP) is a rare form of localized plasma cell tumor that arises most often in the head and neck region. We present an unusual case of EMP of the palatine tonsil from a tertiary care university hospital. We discuss the histopathologic and radiologic evaluation as well as treatment of EMP.